A orientação fonoaudiológica a pais e a capacitação da linguagem de seus filhos - Moreira, Mirna Dorneles (2007)
This study had as objective to verify the effectiveness of the information about the language and the directed speaking development to a group of parents of children with alterations in these areas. The sample was composed of 23 children who were in the wait list of the Phonoaudiology sector in the City department of Health and Environment from Rosario do Sul-RS , they were between 4 and 8 years old, divided in two groups: a study group composed of 11 children and a control group composed of 12 children. The children were submitted to a speaking evaluation and to a language evaluation. The parents the eleven children from the study group participated of informative meetings that occurred fortnightly, for one hour, totalizing eight meetings, in a period of four months, in other words, from August to November of 2005. During these meetings they received information about how the communication process happens and the factors that influence it, beyond activities of language and speaking stimulation to be done at home with the child. The parents the twelve children from the control group didn't have access to these information. In the end of the meetings, the children from the two groups were again submitted to a speaking evaluation and to a language evaluation using the same instruments from the initial evaluation. For analysis of the collected data, the results of the initial valuation were compared with the ones from the final evaluation of each group and also the results between the groups, verifying the interaction between evaluation and group. This analysis was made through the Variance Analysis, using the delineation in repeated measures, accomplished through the Proc Mixed of software SAS version 9.1 - Type 3 Tests of Fixed Effects, complemented by the Multiple Comparisons Test of Tukey, to the significance level of 5%. The results showed that only the language comprehension ability and the total of words evoked during the phonological evaluation didn't present significant interaction between evaluation and group. However, the abilities of conceptualization and expression of language, the joint examination and the phonological evaluation, demonstrated significant interaction between evaluation and group, indicating through the comparison between the initial and final evaluations experienced in the children, that the aspects referring to the language improved significantly in the study group, where the parents received orientations, evidencing that these orientations influenced the results. In the control group, where the parents didn't receive orientations, this improvement was not significant. It was also possible to take care of a bigger number of people, reducing the waiting time for an attendance, controlling the demand.